2021
DOI: 10.3390/min11121374
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Rare Earth Elements from NdFeB Magnets without Mechanical Pretreatment by Sulfuric (H2SO4) and Hydrochloric (HCl) Acids

Abstract: A simplified approach for rare earth elements leaching from NdFeB (neodymium-iron-boron) magnets was investigated. The possibility of simplifying the magnet recycling process by excluding grinding, milling and oxidative roasting unit operations was studied. Attempts to skip the demagnetization step were also conducted by using whole, non-demagnetized magnets in the leaching process. The presented experiments were conducted to optimize the operating conditions with respect to the leaching agent and its concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…In our previous study, we proposed a simplified process of hydrometallurgical NdFeB magnet recycling [24]. Its simplicity is a result of omitting the unit operations of crushing, grinding, and roasting before leaching.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we proposed a simplified process of hydrometallurgical NdFeB magnet recycling [24]. Its simplicity is a result of omitting the unit operations of crushing, grinding, and roasting before leaching.…”
Section: Introductionmentioning
confidence: 99%
“…Klemettinen excluding various pretreatment steps, viz., grinding and oxidative roasting. 21 The main aim of the present investigation is to incorporate statistical modeling with a conventional leaching process to study the effect of process parameters on the response variables using response surface methodology−Box Behnken design (RSM-BBD). The study focuses on process optimization and in-depth study of the impact of process parameters on the leaching process, as well as their reciprocal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that pretreatment steps such as grinding with NaOH and then roasting at different temperatures aided in selective leaching. Klemettinen et al developed a simplified approach for leaching of REEs from scrap NdFeB magnets by excluding various pretreatment steps, viz., grinding and oxidative roasting …”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been carried out to investigate the effect of mineral acids leaching reagents, such as sulfuric [6][7][8], hydrochloric [8][9][10], and nitric [10] acids, and organic acids leaching reagents [11][12][13], such as citric, acetic, formic, and tartaric acids, on the leaching efficiency of REPMs. Although the results showed that both types of acids can dissolve the metals in REPMs, environmental issues have caused more attention to be drawn toward using organic acids as green solvents.…”
Section: Introductionmentioning
confidence: 99%